A Highly Efficient Graphene Gold Based Green Supercapacitor Coin Cell Device for Energy Storage - Singh, D; Vivas, L (Frontiers Media S.A., 2022)
Inclination to exploit renewable energy and their potential storage by facile, cost-effective, and above all in a green way are exactly what the current alternative energy research is looking for. The high-performance supercapacitor devices made up with the electrode materials synthesized in a simple and ecofriendly way are in utmost demand and the ultimate goal for widespread commercialization. Keeping these points in view, one pot green synthesis of active electrode material rGO-Au composite is achieved which not only performs as a very good supercapacitor in three-electrode configuration but also demonstrates extremely well as a coin cell device, ready to use. Ascorbic acid, which is commonly found in citrus fruits, plays an important role to reduce graphene oxide into rGO and simultaneously gold salt into gold nanoparticles, resulting in rGO-Au composite. The maximum recorded specific capacitance by CV measurement is 303.02 Fg−1 at a scan rate of 5 mVs−1. Hindrance in the commercialization is caused by the differences in the supercapacitor performances between three electrode configurations and finally the proposed device. Here the proposed coin cell device exhibits maximum areal and mass specific capacitance of 62.43 mFcm−2 and 56.09 Fg−1, respectively, that is very high among all reported graphene based composite devices benefitted over with commercially viable high capacity retention up to 80% even after 10,000 cycles. The proposed device demonstrates high energy density (∼ ED = 7.79 Wh/Kg) comparable to batteries and an optimum power density (∼ PD = 2512.9 W/Kg) close to supercapacitor insinuating it is an effective green supercapacitor for commercialization. Copyright © 2022 Vivas and Singh.